Acetylene-linked conjugated polymers for sacrificial photocatalytic hydrogen evolution from water. Issue 32 (30th July 2021) - Liu, Lunjie; Kochman, Michał A.; Xu, Yongjie; Zwijnenburg, Martijn A.; Cooper, Andrew I.; Sprick, Reiner Sebastian
Abstract : Acetylene-linked conjugated organic polymers have shown potential as photocatalysts for hydrogen production from water and their performance was studied by varying building blocks systematically. Abstract : Conjugated organic polymers have shown potential as photocatalysts for hydrogen production by water splitting. Taking advantage of a high throughput screening workflow, two series of acetylene-linked co-polymers were prepared and studied for their potential as photocatalysts for sacrificial hydrogen production from water. It was found that a triethynylbenzene-based polymer with a dibenzo[ b, d ]thiophene sulfone linker (TE11) had the highest performance in terms of hydrogen evolution rate under visible illumination in the presence of a sacrificial hole-scavenger. Synthetically elaborating the triethynylbenzene linker in TE11 by changing the core and by introducing nitrogen, the resulting hydrogen evolution rate was further increased by a factor of nearly two.